Systematic improvement of web applications design - Garrido, Alejandra
Web applications are usually characterized by a rapid development process and continu- ous evolution. This evolution implies growth of the graph of pages and navigation paths, as well as new functionality and new data made available to the user. Measurement of the system usability, periodic or after a time of growth, is crucial to the system's evolution in the line of design maturity and to prevent the system from decay. This kind of evolution is one of the main practices of agile methods, in which design improvement occurs daily during development and often during maintenance. In this paper we propose a list of changes for the design models of a Web appli- cation and when they may be applied, in order to improve the application's usability while preserving its functionality. The purpose of the proposed changes is to improve the maturity of the design instead of adding new features; we call them Web design improve- ments. This paper starts a catalogue of Web design improvements for the navigation and presentation models of a Web application. Since changing these models has direct impact on the user experience with the application, our Web design improvements aim at improving the external quality and user experience.